O lúdico no ensino da matemática na EJA: um subsídio contra a evasão escolar - SOUZA, Fábio Monteiro (2022)
This Course Completion Work (TCC) deals with the play as a subsidy for the teaching of Mathematics in the EJA, with the perspective of reducing school dropout. It refers to a study that developed in two moments: the first in the experience of the supervised internship at a school in the state of Castanhal-Pará, which caused the motivation for the study, and the second, based on a research and literature on the subject. The exploratory study, with a qualitative approach, had students as collaborators and a Mathematics teacher from a group of 4th stage of Youth and Adult Education (EJA). Research papers included observations during the internship and a semistructured interview with a talk wheel, as well as printed and online books that deal with the subject in question. The information acquired during the experience with the class evidences that the avoidance among other reasons can also be motivated by the cold form as the lessons occur, as well as the references like Novaes (1987); Gadotti and Romão (2002); Brazil (2004), Libâneo (2004), Teixeira (2010); Huizinga (2010); Santos (2011), among others, who deal with the EJA and indicate that Ludicidade can develop the learning of adult students, provided that the games, the toys and the games approach the contents to the experiences of the life in society, so that teaching and do not get in the way of teaching and learning.